2015
DOI: 10.1186/s13046-015-0256-0
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoural neutrophils negatively regulate adaptive immunity via the PD-L1/PD-1 signalling pathway in hepatocellular carcinoma

Abstract: BackgroundPD-L1 expression on neutrophils contributes to the impaired immune response in infectious disease, but the detailed role of PD-L1 expression on neutrophils in HCC remains unclear.MethodsWe investigated the phenotype and morphology of neutrophils infiltrated in tumour tissues from both patients with HCC and hepatoma-bearing mice.ResultsWe found that neutrophils dominantly infiltrated in the peritumoural region. The neutrophil-to-T cell ratio (NLR) was higher in peritumoural tissue than that in the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(191 citation statements)
references
References 36 publications
4
174
0
2
Order By: Relevance
“…Interestingly, inflammatory factors were not in equivalent levels in the intratumoral and peritumoral sites. IL-1β, GM-CSF, G-CSF, TnF-α, and IL-6 were significantly increased in tumor tissues compared with adjacent non-tumor tissues (55,56). IL-6 and IL-8 released from myofibroblasts were found to upregulate S100A8/A9 in tumor-infiltrated myeloid cells (57).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inflammatory factors were not in equivalent levels in the intratumoral and peritumoral sites. IL-1β, GM-CSF, G-CSF, TnF-α, and IL-6 were significantly increased in tumor tissues compared with adjacent non-tumor tissues (55,56). IL-6 and IL-8 released from myofibroblasts were found to upregulate S100A8/A9 in tumor-infiltrated myeloid cells (57).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study recently indicated that a high level of peritumoral neutrophil infiltration and neutrophil-to-lymphocyte T cell ratio (pNLR) correlated with poor patient survival after curative resection. This study also showed that peritumoral neutrophils negatively regulated adaptive immunity via the PD-L1/PD-1 signaling pathway in HCC patients [31]. Accordingly, we speculated that PD-L1 expression in peritumoral infiltrating immune cells may also be a poor prognostic marker partly resulting from peritumoral infiltration of PD-L1 positive neutrophil interacting with PD-1 positive CD8 + T cells to inhibit and destroy T-cell-mediated antitumor immunity.…”
Section: Discussionmentioning
confidence: 70%
“…Levels of immunosuppressive cytokines IL‐10 and TGF‐β are upregulated in HCC patients at the same time as pro‐inflammatory IFN‐γ levels are downregulated 88 . An increased percentage of circulating and tumour‐infiltrating CD8 + T cells express PD‐1 while tumour cells and tumour‐associated monocytes and neutrophils express upregulated PD‐L1 and CD47 levels in HCC patients 89 , 90 , 91 , 92 . The numbers of myeloid‐derived suppressor cells are also elevated in HCC patients 88 , 93 .…”
Section: Subversion Of the Immune System During Hcc Developmentmentioning
confidence: 99%
“…88 An increased percentage of circulating and tumourinfiltrating CD8 + T cells express PD-1 while tumour cells and tumourassociated monocytes and neutrophils express upregulated PD-L1 and CD47 levels in HCC patients. [89][90][91][92] The numbers of myeloid-derived suppressor cells are also elevated in HCC patients. 88,93 Furthermore, activation of the c-Myc oncogene switches on PD-L1 and CD47 expression in hepatocytes, 94 raising the possibility that oncogenes may directly regulate PD-L1 levels to subvert surveillance.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%